Immunisation against αIIbβ3 and αvβ3 in a type 1 variant of Glanzmann’s thrombasthenia caused by a missense mutation Gly540Asp on β3 - Wihadmadyatami, Hevi; Röder, Lida; Berghöfer, Heike; Bein, Gregor; Heidinger, Kathrin; Sachs, Ulrich J.; Santoso, Sentot (Thrombosis and Haemostasis, 2016)
Treatment of bleeding in patients with Glanzmann’s thrombasthenia (GT) can be hampered by iso-antibodies against the αIIbβ3 integrin, which cause rapid clearance of transfused donor platelets. Type 1 GT patients with a total absence of αIIbβ3 from the platelet surface are known to be susceptible to form such isoantibodies. In this study, we describe a type 1 GT patient with a missense mutation (Gly540Asn) located in the EGF3 domain of the β3 integrin subunit. Cotransfection analysis in CHO cells demonstrates total absence of αIIbβ3 from the surface, based on inappropriate αIIb maturation. The patient’s serum was reactive with αIIbβ3 and αvβ3 integrins in a capture assay, when platelets and endothelial cells were used. Two specificities could be isolated from the patient’s serum, anti-αIIbβ3 and anti-αvβ3 isoantibodies. Both specificities did not interfere with platelet aggregation. In contrast, isoantibodies against αvβ3, but not against αIIbβ3, were able to disturb endothelial cell adhesion onto vitronectin, triggered endothelial cell apoptosis and interfered with endothelial tube formation. This intriguing finding may explain more recently observed features of fetal/neonatal iso-immune thrombocytopenia in children from type 1 GT mothers with intracranial haemorrhage, which could be related to anti-endothelial activity of the maternal antibodies. In conclusion, we give evidence that two isoantibody entities exist in type 1 GT patients, which are unequivocally different, both in an immunological and functional sense. Further research on the clinical consequences of immunisation against αvβ3 is required, predominantly in GT patients of childbearing age.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Glanzmann’s thrombasthenia; platelet function defect; isoimmunisation; αvβ3